The Influence of Human Capital on The Teacher’s job Performance in TK-SD Islam Terpadu Al-Karima Kubu Raya - admin, Ridwan B12112021 (Jurnal Manajemen Update, 2016)
The purpose of this study was to analyze the influence of Human Capital that consists of the individual capability, the individual motivation, leadership, organizational climate and workgroup effectiveness on teacher job performance in the TK-SD Islam Terpadu Al-Karima Kubu Raya.The used method in this research is descriptive method where the sample is the teachers in TK-SD Islam Terpadu Al-Karima Kubu Raya with the total 30 people. Data analysis was performed using SPSS 16 and using multiple linear regression testing. The results of this study indicate that individual capability, leadership and organizational climate influence on teacher job performance while individual motivation and workgroup effectiveness does not affect the performance of teachers in TK-SD Islam Terpadu Al-Karima Kubu Raya. Keywords: Human Capital, Al-Karima, Kubu Raya, Teacher Performance